SOSIALISASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP ORGANISASI SOSIAL FATAYAT DI DESA GENTING KECAMATAN TEMBALANG KOTA SEMARANG - Maulia Indana Zulfa; Abidin, Zaenal; Mar’atus Sholikah (Tahta Media Grup, 2025)
The purpose of this community service is to increase public awareness and participation in the Fatayat social organization through outreach activities in Genting Village, Tembalang District, Semarang City. It is also hoped that it can increase public understanding and awareness regarding the importance of active involvement in social organizations through structured and participatory outreach activities. This community service was carried out at the Genting Village Hall, Tembalang District, Semarang City. Participants in this community service consisted of: regular female religious study group members from Genting Village, Tembalang District, Semarang City. This community service used lecture and question and answer methods in a discussion forum at the Genting Village Hall, Tembalang District, Semarang City. This activity also gave rise to the initiative to form a community working group to support social programs in the village. The constraints that occurred during the training were that there were several religious study group members who had not been touched by the outreach